(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the skill of creating an image in Shukur Kholmirzayev’s novels. In particular, on the example of the writer’s novel "Olabo’ji", the methods of revealing the character of the hero, psychological means of depiction, internal monologue, portrait and the functional significance of artistic detail are highlighted. The article scientifically substantiates the writer’s skill of deeply and impressively expressing the national spirit, problems of the era and human experiences in creating an image based on realistic principles. The interrelation of the system of images, the role of the conflict and the image of the environment in the formation of the character of the hero are also analyzed.